Performance analysis of a tractor - power harrow system under different working conditions. (February 2021) - Balsari, P.; Biglia, A.; Comba, L.; Sacco, D.; Eloi Alcatrão, L.; Varani, M.; Mattetti, M.; Barge, P.; Tortia, C.; Manzone, M.; Gay, P.; Ricauda Aimonino, D.
Abstract : Tillage is one of the most important operations in the preparation of land for growing crops. Among secondary tillage implements, power harrows, which have a series of PTO-driven rotors which rotate about their vertical axis, are widely adopted in soil-working operations. Typically, this kind of implement is highly energy consuming, due to the heavy mechanical loads required to pull the harrow and the PTO (Power Take-Off) torque needed to drive the rotors. This paper reports the results of extensive in-field experimentation in which the relationship between the operating conditions of a tractor - power harrow system and the mechanical loads (i.e. PTO torque and draught) were investigated in two different test site fields. The test parameters consisted of: nominal tractor speed (3, 6, 9 and 12 km h −1 ), nominal working depth (6, 9 and 15 cm) and rotor speed (285 and 411 rpm) at a PTO speed of 1000 rpm. The data was statistically analysed by means of a linear mixed effect model to assess the differences in the tractor - harrow system performances measured under different working conditions. The presented results show which operating conditions can be favourable regarding energy and fuel consumption as this information may be very useful to farmers to reduce costs. Moreover, the measured mechanical loads concerning PTO torque and draught may also be beneficial for manufacturers to improve the design of these kinds of implements. Graphical abstract: Image 1 Highlights: Mechanical loads and fuel consumption values for tilling operations are reported. The average PTO torque values were in the range of 80–620 Nm. The average draught values were in the range of 4–13 kN. Power and energy values per unit of volume and surface of tilled soil are reported.